Rare presentation of pancreatitis secondary to intussusception of duodenal duplication cyst, a pediatric case report - Valentina Shakhnovich; Jennifer Colombo; Amita A. Desai; Shawn D. St. Peter (Elsevier, 2014)
Duodenal duplication cysts are rare congenital malformations of which there is limited literature in the pediatric population. The most common presentation in symptomatic patients is abdominal pain and pancreatitis. We present a case of a 14 year old female that presented with emesis, abdominal pain, weight loss, and admission biochemical profile concerning for acute pancreatitis in conjunction with severe hypochloremic, hypokalemic metabolic alkalosis. Further imaging was highly suggestive of duodeno-duodenal intussusception causing obstruction of the pancreatic duct. Patient was taken emergently to the operating room for exploration. Patient underwent laparoscopic assisted reduction of intussusception and resection of duodenal duplication cyst. Patient tolerated the surgery well, and was able to be discharged home in stable condition soon after. There have been no cases reported in the literature that describe pancreatitis secondary to intussusception of duodenal duplication cyst. When diagnosed early, these patients can be safely managed laparoscopically even in emergent settings.